Effects of Probiotic Supplementation on the Gut Microbiota and Antibiotic Resistome Development in Preterm Infants - Esaiassen, Eirin; Hjerde, Erik; Cavanagh, Jorunn Pauline; Pedersen, Tanja; Andresen, Jannicke H.; Rettedal, Siren I.; Støen, Ragnhild; Nakstad, Britt; Willassen, Nils P.; Klingenberg, Claus (Frontiers in Pediatrics, 2018)
Objectives: In 2014 probiotic supplementation (Lactobacillus acidophilus and Bifidobacterium. longum subspecies infantis; Infloran ®) was introduced as standard of care to prevent necrotizing enterocolitis (NEC) in extremely preterm infants in Norway. We aimed to evaluate the influence of probiotics and antibiotic therapy on the developing gut microbiota and antibiotic resistome. Study design: A prospective, observational multicenter study in six tertiary-care neonatal units. We enrolled 76 infants; 31 probiotic-supplemented extremely preterm infants < 28 weeks gestation, 35 very preterm infants 28-31 weeks gestation not given probiotics and 10 healthy full-term control infants. Taxonomic composition and collection of antibiotic resistance genes (resistome) in fecal samples, collected at 7 and 28 days and 4 months age, were analyzed using shotgun metagenome sequencing. Results: Mean (SD) birth weight was 825 (178) g and 1290 (220) g in preterm infants exposed and not exposed to probiotics, respectively. Two extremely preterm infants receiving probiotic developed NEC. At 7 days age we found higher median relative abundance of Bifidobacterium in probiotic supplemented infants (64.7%) compared to non-supplemented preterm infants (0.0%) and term control infants (43.9%). Lactobacillus was only detected in small amounts in all groups, but the relative abundance increased up to 4 months. Extremely preterm infants receiving probiotics had also much higher antibiotic exposure, still overall microbial diversity and resistome was not different than in more mature infants at 4 weeks and 4 months. Conclusion: Probiotic supplementation may induce colonization resistance and alleviate harmful effects of antibiotics on the gut microbiota and antibiotic resistome. The early high abundance of Bifidobacterium in probiotic-supplemented extremely preterm infants may suggest that a gradual increase in supplementation is warranted. Clinical Trial Registration: Clinicaltrials.gov: NCT02197468. https://clinicaltrials.gov/ct2/show/NCT02197468